2023
DOI: 10.1007/s40121-023-00827-9
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Antibiotic Resistance Trends Nationally in Gram-Negative Bacteria Across United States Veterans Affairs Medical Centers, 2011–2020

Abstract: Introduction Gram-negative resistance is a well-acknowledged public health threat. Surveillance data can be used to monitor resistance trends and identify strategies to mitigate their threat. The objective of this study was to assess antibiotic resistance trends in Gram-negative bacteria. Methods The first cultures of Pseudomonas aeruginosa , Citrobacter , Escherichia coli , E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The decrease in culture-positive cases may reflect an increasing tendency to suspect and treat patients for sepsis who turn out not to have sepsis in retrospect. Alternatively, it is possible that community-onset sepsis cases caused by resistant pathogens have truly decreased; indeed, other studies have reported recent declines in community-onset MRSA, Pseudomonas , and Acinetobacter infections . This may reflect the fitness cost of resistance, antibiotic stewardship efforts in both inpatient and outpatient settings, greater attention to hospital infection prevention programs, and changing antibiotic use practices in the environment and in animals .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in culture-positive cases may reflect an increasing tendency to suspect and treat patients for sepsis who turn out not to have sepsis in retrospect. Alternatively, it is possible that community-onset sepsis cases caused by resistant pathogens have truly decreased; indeed, other studies have reported recent declines in community-onset MRSA, Pseudomonas , and Acinetobacter infections . This may reflect the fitness cost of resistance, antibiotic stewardship efforts in both inpatient and outpatient settings, greater attention to hospital infection prevention programs, and changing antibiotic use practices in the environment and in animals .…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it is possible that community-onset sepsis cases caused by resistant pathogens have truly decreased; indeed, other studies have reported recent declines in community-onset MRSA, Pseudomonas , and Acinetobacter infections. 35 , 36 , 37 This may reflect the fitness cost of resistance, antibiotic stewardship efforts in both inpatient and outpatient settings, greater attention to hospital infection prevention programs, and changing antibiotic use practices in the environment and in animals. 38 Notably, increases in multidrug-resistant organisms were observed in US hospitals during the early COVID-19 pandemic era; however, these were primarily driven by hospital-onset rather than community-onset infections.…”
Section: Discussionmentioning
confidence: 99%
“…[5] There is evidence that Citrobacter possesses intrinsic resistance to carboxypenicillins and aminopenicillins; however, multiple strains have shown at least some degree of susceptibility to piperacillin-tazobactam 92%, cefepime 97.7%, and ceftriaxone 81.6%. [5,7] Additionally, as C. koseri does not harbor the chromosomal AmpC beta-lactamase gene, which decreases the efficacy of the beta-lactam class of antibiotics, it is reasonable to begin empiric ceftriaxone while awaiting formal susceptibility results. [8] While Citrobacter is rarely found to cause septic arthritis, the potential consequences of untreated bacteremia underscore the importance of maintaining a broad differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of both extreme drug resistant (XDR) and pan drug resistant (PDR) 5 A. baumannii strains poses a challenge for clinical therapeutics. Furthermore, MDR A. baumannii is often associated with inappropriate empiric therapies which contribute to high case fatality rates 6 . Acinetobacter baumannii isolates manifesting XDR are defined as being highly resistant to three or more classes of antibiotics, including fluoroquinolones, penicillins, cephalosporins with inhibitor combinations and aminoglycosides.…”
Section: Introductionmentioning
confidence: 99%